Protective effect of Luffa cylindrica fermentation liquid on cyclophosphamide-induced premature ovarian failure in female mice by attenuating oxidative stress, inflammation and apoptosis - Yueying Feng; Wei Zhang; Xiaowei Xu; Wanzhen Wang; Yuanyuan Xu; Mengqi Wang; Jinfeng Zhang; Hengyi Xu; Fen Fu (Journal of Ovarian Research, 2024)
Abstract Premature ovarian failure (POF) is a leading cause of women’s infertility without effective treatment. The purpose of this study was to investigate the protective effects of Luffa cylindrica fermentation liquid (LF) on cyclophosphamide (CTX) -induced POF in mice and to preliminarily investigate the underlying mechanisms. Thirty-two Balb/c mice were divided into four groups randomly. One group served as the control, while the other three received CTX injections to establish POF models. A 14-day gavage of either 5 or 10 μL/g LF was administered to two LF pretreatment groups. To analyze the effects of LF, the ovarian index, follicle number, the levels of serum sex hormones, superoxide dismutase (SOD), glutathione (GSH), malondialdehyde (MDA), inflammatory factors, and apoptosis of the ovarian cells were measured. The effects of LF pretreatment on the expression of TLR4/NF-κB and apoptosis pathways were also evaluated. We found that LF pretreatment increased the ovarian index and the number of primordial and antral follicles while decreasing those of atretic follicles. LF pretreatment also increased the serum levels of estradiol (E2) and anti-Müllerian hormone (AMH), while decreasing those of luteinizing hormone (LH) and follicle-stimulating hormone (FSH). Furthermore, LF pretreatment increased the levels of SOD and GSH in the ovaries, while decreasing those of MDA, tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β). LF administration reduced the amount of TUNEL+ ovarian cells and the levels of TLR4 and NF-κB P65 protein expression. In conclusion, LF has antioxidant, anti-inflammatory as well as anti-apoptotic effects against CTX-induced POF, and the inhibition of TLR4/NF-κB and apoptosis pathways may be involved in its mechanisms. Graphical Abstract